ANALISIS PENGARUH PEMBIAYAAN MUDHARABAH, MURABAHAH, MUSYARAKAH TERHADAP PROFITABILITAS BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) DI JAWA TENGAH PERIODE 2020-2022 - Imron, Ali; Ariyanti, Rizka (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2023)
The purpose of the study was to determine and analyze the effect of Mudharabah (X1), Murabahah (X2), Musyarakah (X3) on the profitability of Islamic People's Financing Banks (BPRS) in Central Java.Samples were taken using purposive sampling method. The population in this study are all BPRS that have and are still registered with OJK in Central Java for the period 2020-2022. From a population of 26 BPRS obtained 11 BPRS as a sample with a sample with an observation period of three years (2020-2022). Data were analyzed using multiple linear regression. The results of this study indicate that the Mudharabah variable (X₁) has a quality effect on Profitability (Y) with a significance of 0.007 and a tcount value of 2.940> ttable 2.040. Mudarabah variable (X₂) affects the quality of Profitability (Y) with a significance value of 0.001 and a tcount value of 3.639> ttable 2.040. Musyarakah variable (X₃) has no effect on the quality of Profitability (Y) with a significance of 0.089 and a tcount value of 1.774 < t table 2.040. Mudharabah (X₁), Murabahah (X₂), Musyarakah (X₃) variables, have a significant effect together or overall on Profitability (Y) with a value of Fcount 6.217> Ftable 2.930 or a significance value of F 0.003ᵇ < α 0.05 at Islamic People's Financing Banks (BPRS) in Central Java for the 2020-2022 Period.